Hasan Al-Banna's Concept of Thought in the Perspective of Islamic Education - Aswanda, Jais; Hulawa, Djeprin E.; Dewi, Eva (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2023)
This article attempts to examine and understand Hasan Al-Banna's thoughts from an Islamic Education Perspective. And the thought of Islamic education is a series of work processes of the mind and heart that are carried out seriously in looking at various problems that exist in Islamic education and trying to build an educational paradigm that can become a vehicle for complete guidance and development of students. Hasan Al-Banna is the founder of the Ikhwan al-Muslimin movement, one of the largest and most influential Islamic organizations in the 20th century. As for this research, which is in the form of library research, in the process of collecting data, the author collects data in the form of information through literature that the author obtains in the form of books or articles, magazines, or seminar results. and other information related to the issue being raised, namely reviewing the thoughts on Islamic education according to Hasan al-Banna. Considering that this research is qualitative research, data analysis was carried out using the following approach: First, a historical approach. Second, the descriptive approach. Each material or data is analysed, analysed, described, and concluded inductively. This research is descriptive analysis. The research results show that the idea of ​​thinking in education is total and holistic, divinely oriented, universal, integrated, balanced, and full of positive and constructive skills. then data analysis was carried out using the following approach: First, a historical approach. Second, the descriptive approach. Each material or data is analysed, analysed, described, and concluded inductively. This research is descriptive analysis. The research results show that the idea of ​​thinking in education is total and holistic, divinely oriented, universal, integrated, balanced, and full of positive and constructive skills. then data analysis was carried out using the following approach: First, a historical approach. Second, the descriptive approach. Each material or data is analysed, analysed, described, and concluded inductively. This research is descriptive analysis. The research results show that the idea of ​​thinking in education is total and holistic, divinely oriented, universal, integrated, balanced, and full of positive and constructive skills.